STRATEGIES OF DIGITALIZATION IN THE CONTEXT OF BUSINESS DIGITAL TRANSFORMATION: TRENDS AND INNOVATIONS - KUSHCH, Anastasiia; PIROGOV, Dmytro; PIROGOV, Yehor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the role of digitalization and its transformative effects on modern business and the economy. It examines the integration of cutting-edge digital technologies such as  artificial intelligence (AI), and cloud computing into various aspects of business operations, focusing on their impact on efficiency, productivity, and innovation. The research highlights how digital transformation is not only about optimizing existing business processes but also about creating new business models that adapt to the ever-changing global market. A significant portion of the article is dedicated to analyzing key aspects of digital transformation, including the redesign of business models and strategies to incorporate emerging technologies. It is emphasized that companies that successfully integrate these technologies can achieve greater competitiveness and sustainability in the digital age. Furthermore, the article outlines the main principles guiding digitalization, which play crucial roles in ensuring successful adoption and integration of digital tools within organizations and also addresses the advantages of digitalization, such as enhanced customer interactions, data-driven decision-making, and the optimization of internal processes.Overall, the article concludes that digital transformation is a vital driver of economic growth and business innovation. The successful implementation of digital strategies can significantly improve business performance, enable companies to remain competitive, and pave the way for future growth. The integration of new digital technologies will continue to shape the global economy, making it essential for businesses to embrace digitalization as a critical component of their long-term strategy.
Keywords: digitalization; integration of modern tools; business process transformation; automation; innovative technologies